Desarrollo de un laboratorio virtual para prácticas de máquinas eléctricas. - Galarza Ludeña, Carlos Livio (2014)
The present work was compiled information that contained theoretical of electrical machines taught in the University National of Loja the career of electromechanical. Whit the practice defined follow whit the models mathematic of every practice to implementation of the virtual laboratory, the follow is like design of diagrams a blocks in the software LabVIEW. Finish builds the frontal screen the every virtual practice. To machines asynchronies graph is the curve characteristic torque-speed of synchronies, the base of graph essential in the variations the speed of synchronies. If resistor variations of rotor the results are different graph. To generator asynchronies is similar whit motors only different is in the glide which is negative. To machines synchronies was make one graph of generator synchronies the terminal voltage whit line current which the factory power they are thus delayed. To motor synchronies the graph is curve in V or curve of Morday that definitions is only line current and phase current. To machines static or more now in the word three phase transformer is similar like the asynchronies motors of the calculations is equal the base of graph is the voltage regulations when variations load, can maybe whit the factory power advancement, unit and delay.